Collective colouring in danmu comments on Bilibili. (March 2022) - Teng, Man; Chan, Brian Hok-Shing
Abstract: Social media provide their users with various semiotic resources for meaning-making in different modes (e.g., text, image, colour, etc.). While non-linguistic modes have been recognized to play an important role in meaning-making, less attention has been paid to the creative use of colour on social media. This paper contributes to this area by studying the use of colour when video comments are produced in the form of danmu on a Chinese video-sharing website Bilibili . Drawing on social semiotic multimodal analysis, this paper conceptualizes colours as a semiotic mode, in which specific colours are "turned on" to fulfill two functions, namely: a) enacting fan relation and b) expressing judgement and affect triggered by video contents, signaling a change of context from video commenting to a collective act of colouring video comments. Besides, colours are used by danmu comment makers to create cohesion in danmu comments and marshal their comments into the collective colouring act. Based on these findings, we suggest that colour also works as a contextualization cue, whose function has to be understood in conjunction with cultural knowledge, the texts of the comments and contextual references provided by videos. Furthermore, rather than being subordinate to language/text, colour is a crucial semiotic mode in the meaning-making process of danmu comments, which adds further layers to understanding the discourse and semiotic practices on Chinese social media.